Rising Stars_Garba_Keziah - Garba, Keziah (My University, 2023)
This presentation explores the pivotal roles of human capacity development in strengthening women's competencies in the Sub-Saharan nuclear industry.
Keywords: Human capacity building; Gender policy; nuclear energy